Insight on microstructure and mechanical properties of 40 mm thick-walled ferromagnetic super-MSS by magnetic-field-assisted narrow gap GTAW - Fuxiang Li; Yibo Liu; Haoyu Kong; Huisheng Ren; Yujie Tao; Qinghua Zhang; Qingjie Sun (Journal of Materials Research and Technology, 2023)
In this work, the welding of 40 mm thick-walled ferromagnetic super martensitic stainless steels (super-MSS) welded by magnetic-field-assisted (MFA) narrow gap-gas tungsten arc welding (NG-GTAW) is reported and a defect-free joint is successfully obtained. The variations trends of microstructure and mechanical properties at different positions along the thickness direction of the joint are analyzed. The results show that there are obvious differences in microstructure and properties between different layers of the MSS joint. The strength level of the joint is comparable to that of the base metal. The impact toughness of the middle and bottom layers is much higher than that of the base metal. This is mainly due to the differences in microstructure, such as austenite content, refinement and grain boundary characteristics of martensite observed by OM, SEM, and EBSD. A two-pass filling test is employed to understand the evolution of microstructure and properties of thick-walled super-MSS joint and clarify the self-heat-treatment (SHT) effect between the weld passes by simulation. It is found that during the welding process of thick-walled super-MSS, the adjacently later pass can exert an obvious SHT effect on the bottom layer, which leads to significant refinement of martensitic lath in the weld. Finally, the relation between microstructure and properties of the thick-walled super-MSS joint is revealed.